Generalized layered space-time codes for high data rate wireless communications. - Meixia Tao (IEEE Transactions on wireless communications)
We present the architecture of generalized layered space-time codes (GLST) as a combination of Bell Labs layered space-time (BLAST) architecture and space-time coding (STC) in multiple-antenna wireless communication systems. This approach provides both spectral and power efficiency with moderate complexity. The framework is to partition all the available transmit antennas into groups and apply STC on each group as component codes. Based on the mappings from coded symbols to transmit antenna groups, we can construct different GLST systems. Particularly, horizontal mapping and diagonal mapping are introduced and referred to as HGLST and DGLST respectively. The basic decoding of GLST, under quasi-static flat Rayleigh fading environments and assuming perfectly known channel state information (CSI) at the receiver, combines group interference suppression and group interference cancellation techniques. As a result, the individual STC on each group is decoded serially. To improve the overall system performance, we derive the optimal power allocation among all space-time codewords without requiring the knowledge of CSI at the transmitter and suitable for all GLST systems. We also derive the optimal serial decoding order based on the channel realizations at the receiver for HGLST systems without power allocation. Simulation results show that both can provide much improvement. To further enhance the system performance, we propose a low complexity hard-decision iterative decoding method. This method efficiently exploits full receive antenna diversity and, hence, dramatically improves the system performance which is confirmed by simulation.